Kekerasan pelajar dan ancaman terhadap nilai kehidupan: studi kasus penusukan siswa di salah satu sekolah dalam perspektif qs. Al-māidah ayat 32 - Novarine, Laudhy Octhavia (Maliki Interdisciplinary Journal, 2026)
Violence among students is increasingly emerging as a serious problem in the educational field, indicating that interactions between students are undergoing a negative shift. The stabbing case carried out by a student at one school illustrates that violence in educational environments has reached an alarming level. This study aims to analyze this case through the perspective of Surah Al-Māidah verse 32, a verse that emphasizes that taking or harming one life without justification is comparable to destroying the lives of all humanity. Using a qualitative approach and analysis of religious texts, this study seeks to examine how the main message of this verse can serve as an ethical foundation for efforts to prevent violence in schools. The results show that the lack of character education, weak monitoring systems, and a culture of bullying that is allowed to develop are the main factors in the emergence of these acts. The Qur'anic values ​​in Surah Al-Māidah verse 32 provide important principles about protecting the soul, reducing conflict, and building a social environment that respects human dignity. These results suggest that integrating religious values ​​into the educational system can be the best step to prevent violence among students and strengthen a culture of mutual respect in the school environment.